Impact of Training Set Batch Size on the Performance of Convolutional Neural Networks for Diverse Datasets - Радюк, Павло Михайлович; Radiuk, Pavlo M.; Радюк, П. М. (My University, 2017)
A problem of improving the performance of convolutional neural networks is considered. A parameter of the training set is investigated. The parameter is the batch size. The goal is to find an impact of training set batch size on the performance. To get consistent results, diverse datasets are used They are MNIST and CIFAR-10. Simplicity of the MNIST dataset stands against complexity of the CIFAR-10 dataset, although the simpler dataset has 10 classes as well as the more complicated one To achieve acceptable testing results, various convolutional neural network architectures are selected for the MNIST and CIFAR-10 datasets, with two and five convolutional layers, respectively. The assumption about the dependence of the recognition accuracy on the batch size value is confirmed: the larger the batch size value the higher the recognition accuracy. Another assumption about the impact of the type of the batch size value on the CNN performance is not confirmed.
Radiuk P. M. Impact of Training Set Batch Size on the Performance of Convolutional Neural Networks for Diverse DatasetsInformation / P. M. Radiuk // Technology and Management Science. – 2017. –№ 20. – Р. 20-24. doi: 10.1515/itms-2017-0003
Keywords: Batch siz; convolutional neural network; dataset; testing accuracy; Research Subject Categories::TECHNOLOGY